Targeting Focal Adhesion Assembly by Ethoxyfagaronine Prevents Lymphoblastic Cell Adhesion to Fibronectin - F. Ouchani; J. Devy; A. Rusciani; J. J. Helesbeux; S. Salesse; I. Letinois; D. Gras-Billart; L. Duca; O. Duval; L. Martiny; E. Charpentier (Analytical Cellular Pathology)
Background: Leukemic cell adhesion to proteins of the bone marrow microenvironment provides signals which control morphology, motility and cell survival. We described herein the ability of ethoxyfagaronine (etxfag), a soluble synthetic derivative of fagaronine, to prevent leukemic cell adhesion to fibronectin peptide (FN/V).